Lumber Society on the Industrial Frontier: Burrard Inlet, 1863-1886 - McDonald, Robert (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
From the mid-to-late 19th century, the small settler population in British Columbia formed relatively isolated and highly discrete communities. One of these settlements, on Burrard Inlet, is best understood as the operation of industrial capitalism in a frontier setting. While settlement clustered around two sawmills, the power of capital — expressed through policies of managerial paternalism — was sharply curtailed by the ethnically complex, relatively transient, geographically isolated, and generally unstable nature of lumber society. As a consequence, relations between the companies and the community were much more a negotiated process than a simple exercise of managerial domination. Lumber capitalists could not escape the constraints imposed upon them by the frontier nature of their operation.